Dissociations Between Medial Prefrontal Cortical Subregions in the Modulation of Learning and Action. - Maddox, Jean-Marie; Holland, Peter C. (Behavioral Neuroscience, 2011)
The medial prefrontal cortex (mPFC) has been implicated in various attentional functions. This experiment examined the involvement of mPFC subregions in the allocation of attention in learning and action as a function of the predictive accuracy of cues. Rats with dorsal (encompassing anterior cingulate, prelimbic, and infralimbic cortices) or ventral (encompassing mainly infralimbic and dorsopeduncular cortices and tenia tecta) mPFC lesions were trained in a multiple-choice discrimination task in which operant nosepoke responses to some visual cues were consistently (100%) reinforced (CRF) with food, whereas responses to other visual cues were partially (50%) reinforced (PRF). In challenge tests designed to assess attention in the control of action, responding was directed more to CRF cues than to PRF cues in sham and dorsal mPFC-lesioned rats, but ventral mPFC-lesioned rats showed similar levels of responding to both CRF and PRF cues. Nevertheless, when given a choice between simultaneously presented CRF and PRF cues in a cue competition test, all groups responded more to CRF cues. In a subsequent Pavlovian overshadowing phase designed to assess attention in the acquisition of new learning, previously trained CRF cues overshadowed conditioning to novel auditory cues more than did PRF cues in dorsal mPFC-lesioned rats, whereas the opposite pattern was observed in sham and ventral mPFC-lesioned rats. These results suggest a dissociation within the mPFC in the use of reinforcement prediction information to allocate attention for new learning and for the control of action. Reprinted by permission of the publisher.